Ketidaksantunan Interaksi Jual Beli Akun Maz Aruel di TikTok: Analisis Siber Pragmatik Perspektif Jonathan Culpeper - Firnanda, Aldi; Putikadyanto, Agus Purnomo Ahmad; Adriana, Iswah; Wardani, Mila Ayu Sri; Ihsan, Zainuri (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the strategy of impoliteness in online buying and selling interactions of Madurese people using a cyber pragmatic approach. Impoliteness is a language behavior that violates the norms of politeness, causing feelings of discomfort, offense, and insult to the interlocutor. The purpose of this study is to analyze the form of impoliteness in online buying and selling interactions from Jonathan Culpeper’s perspective. This study uses a qualitative descriptive method. Data were obtained through a non-participatory observation method of 100 TikTok videos of buying and selling interactions uploaded to the social media account "Maz Aruel." The results of the study show that the strategies of impoliteness from Jonathan Culpeper’s perspective used include direct, positive, negative impoliteness, pseudo-politeness, and eliminating politeness. These findings indicate that digital media has become a new space for expressing impoliteness in Madurese people’s buying and selling interactions. The utterances show violations of Jonathan Culpeper’s principles of politeness in various ways, through a cyber lens, how speech strengthens or modifies the expression of impoliteness.